2018
DOI: 10.3390/rs10111775
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Change Detection of Forest/Grassland and Cropland in the Loess Plateau of China Using All Available Landsat Data

Abstract: Accurate identification of the spatiotemporal distribution of forest/grassland and cropland is necessary for studying hydro-ecological effects of vegetation change in the Loess Plateau, China. Currently, the accuracy of change detection of land cover using Landsat data in the loess hill and gully areas is seriously affected by insufficient temporal information from observations and irregular fluctuations in vegetation greenness caused by precipitation and human activities. In this study, we propose a method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Based on the values of NDVI and in the interpretation of Google Earth images to identify and to quantify the vegetation change during the analysis period (1987-2017), we applied an NDVI thresholding [45,46] to classify NDVI into three classes: (1) NDVI values below to 0.2 were considered as low-density vegetation (2) NDVI values between 0.2 and 0.5 were considered as moderate-density vegetation and (3) NDVI values higher than 0.5 were considered as high-density vegetation. This classification depends on the soil type and, in this case, is based on the knowledge of the study area characteristics.…”
Section: Ndvi Classificationmentioning
confidence: 99%
“…Based on the values of NDVI and in the interpretation of Google Earth images to identify and to quantify the vegetation change during the analysis period (1987-2017), we applied an NDVI thresholding [45,46] to classify NDVI into three classes: (1) NDVI values below to 0.2 were considered as low-density vegetation (2) NDVI values between 0.2 and 0.5 were considered as moderate-density vegetation and (3) NDVI values higher than 0.5 were considered as high-density vegetation. This classification depends on the soil type and, in this case, is based on the knowledge of the study area characteristics.…”
Section: Ndvi Classificationmentioning
confidence: 99%
“…To solve this problem, the riparian vegetation degradation in the river terrace was used to represent the building construction in the river terrace, and NDVI was employed to discriminate the river channel-built-up area interface in this study. In addition, a multi-year criterion in the detection rules [40] is helpful to guarantee that the rules are not satisfied by an accidental vegetation change caused by rainfall or anthropogenic factors, thus improving the detection accuracy. Note that, due to local farmers growing crops in the river terrace, the land-cover type of the river terrace is always vegetation, which can be easily monitored using NDVI time-series.…”
Section: Application Of Detection Methods For River Channel Occupationmentioning
confidence: 99%
“…The pixels with an NDVI value above 0.21 were assigned as non-built-up. For each pixel, the NDVI time-series of the pixels within the built-up area interpreted by GF-2 high-resolution images were assessed by referencing the detection rules of the previous study of Wang et al [40], as follows.…”
Section: River Channel Dynamic Detection Using Ndvi Time-series and Hmentioning
confidence: 99%
“…Specifically, it has been established that there is no statistical difference (p = 0.303) between changes in coral habitat areas as observed by the Coral Reef Evaluation and Monitoring Project (CREMP) and change detection analysis conducted using a combination of Landsat missions [41]. Additional validation studies demonstrated that change analysis conducted based on Landsat 5, Landsat 7, and Landsat 8 was accurate with an overall accuracy of 88.9% ± 1.0% and a kappa coefficient of 0.86 [46]. This study expands upon the previous limited scope analyses by applying a classifier to two new sites [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 96%